Scientific Opinion on the safety and efficacy of hexamethylene tetramine as a silage additive for pigs, poultry, bovines, sheep, goats, rabbits and horses. (18th February 2015) - ,; ,
Abstract: Hexamethylene tetramine (HMTA) is a technological additive intended to improve the ensiling process of forage for pigs, poultry, bovines, sheep, goats, rabbits and horses when used at a maximum concentration of 600 mg HMTA/kg of fresh forage. The residual concentration of HMTA plus formaldehyde, its degradation product, is significantly reduced in silage after three months' ensiling. Considering that no data were provided on the qualitative and quantitative composition of the residues in silage, conclusions cannot be drawn on the safety of HMTA for the target species. The proposed use of HMTA as a silage additive would not increase consumer exposure to the parent compound, its major metabolite formaldehyde or N ‐nitrosodimethylamine to an extent that would pose an appreciably increased health risk to the consumer. HMTA is irritant to the skin, eyes and mucous membranes and it is a skin and respiratory sensitiser. Farmers may be exposed to ammonia and formaldehyde while opening the silo. Formaldehyde is a strong irritant, a potent skin and respiratory sensitiser and a proven human carcinogen by the respiratory route. Measures should be taken to ensure that the respiratory tract, skin and eyes of any person handling the product are not exposed to any dust, mist or vapour generated by the use of HMTA. Similar protective measures are needed for any person handling silage treated with this product. It is expected that the use of HMTA as a silage additive at the proposed concentration would not pose a risk to the environment. The combination of HMTA and sodium nitrite used in the efficacy studies has the potential to improve the ensiling of forage by reducing butyric acid production and proteolysis, pH and dry matter loss. However, with the limited data available, the Panel is unable to conclude on the efficacy of HMTA when used alone.